Legumes As Nitrate Catch Crops During the Dry-To-Wet Transition in Lowland Rice Cropping Systems - George, Thomas; Ladha, J.K.; Garrity, Dennis P.; Buresh, Roland J. (Wiley, 1994)
In tropical rice (Oryza sativa L.) lowlands, NO3‒ assimilation by plants during the transition from the dry to the wet season can preclude NO3‒ loss upon soil flooding and permit recycling of this N. In a 2‐yr field study in an Alfisol in the Philippines, we examined the role of legume crops and weeds during the dry‐to‐wet (DTW) transition in conserving and/or recycling soil NO3‒ that accumulated under varied dry‐season fallow management. During the May‐to‐July DTW transition, Sesbania rostrata (Bremek. and Oberm.), mungbean [Vigna radiata (L.) Wilczek], weedy, and weed‐free treatments were subplots in the February‐to‐May dry‐season mainplots of weedy, weed‐free, and frequently tilled fallows. Legume biological N2 fixation (BNF) was measured by 15N dilution. Depending on dry‐season management, the maximum extracted N (top 60‐cm layer) in the DTW transition ranged from 38 to 164 kg ha−1; this N was 62 to 96% NO3‒. Soil N uptake by weeds ranged from 31 to 46 kg N ha−1, that by mungbean from 29 to 80, and by S. rostrata from 46 to 125. The minimum estimates of DTW transition NO3‒ loss varied from none when plants were present to 107 kg N ha−1 in weed‐free fallows. Legume BNF partially offset NO3‒ loss, although increased soil NO3‒ decreased BNF‐N. Nitrogen fixed ranged from 37 to 63 kg N ha−1 by mungbean and 68 to 154 by S. rostrata. Harvest of mungbean caused negative BNF‐N contribution to the succeeding rice crop in a few cases. In lowland rice‐based cropping systems, weeds are effective in conserving soil N during the DTW transition, but legumes are more suitable nitrate catch crops because they allow the harvest of an economic product or the recycling of more N to a subsequent flooded rice crop.